Training on Optimizing the Application of Accounting Information Systems in MSMEs in the Digital Era of the Indo Global Mandiri Student MBKM Program - Palinggau, Aling; Hertati, Lesi; Terrtiavini, Terrtiavini; Heryati, Agustina; Cahyani, Nani; Puspitawati, Lilis (CV. Proaksara Global Transeduka, 2024)
The purpose of this training is to find out factors such as limited resources, lack of technological understanding, and regulatory uncertainty which are the main obstacles in implementing accounting information systems for MSMEs in the digital era. Training develops training programs that include a basic understanding of accounting information systems, relevant technology, as well as strategies for overcoming obstacles that may arise. The benefit of this training is to provide comprehensive understanding and practical skills to MSME owners and managers, so that they can optimize the application of accounting information systems in business operations. It is hoped that this training will help MSMEs to increase their efficiency, accuracy and resilience in facing the challenges of the digital era, as well as improve the quality of financial reporting.